Anterior Chamber Angle and Volume Do Not Change after Myopic Laser-Assisted In Situ Keratomileusis in Young Patients - Ertuğrul Tan Yassa; Cihan Ünlü (Journal of Ophthalmology)
Purpose. We aimed to investigate whether anterior chamber angle, depth, and volume change after myopic laser-assisted in situ keratomileusis (LASIK) in young patients. Methods. This retrospective study included 29 eyes of 29 patients (15 females and 14 males) between the ages of 18 and 39 years who underwent LASIK for the treatment of myopia. In addition to complete ophthalmic examination, anterior chamber angle (ACA), central anterior chamber depth (ACD), and anterior chamber volume (ACV) were measured by using a Sirius rotating Scheimpflug camera combined with Placido disc corneal topography (CSO, Florence, Italy). Preoperative and postoperative values were compared using paired t-tests. Linear regression was used to evaluate the relationship between changes in refraction and changes in ACA, ACD, and ACV as well as between attempted maximum ablation depth and changes in ACA, ACD, and ACV. Results. The mean age of the study population was 25.5 ± 6.2 years. The mean preoperative and postoperative spherical equivalent values were −3.30 ± 1.92 D and −0.18 ± 0.29 D, respectively. ACV and ACA were not significantly changed after surgery; however, central ACD was significantly decreased (preoperatively = 3.366 ± 0.316 mm vs postoperatively = 3.3 ± 0.298 mm) with a mean difference of 0.066 ± 1.121 mm. There were no significant relationships between changes in refraction and anterior segment dimensions or between attempted maximum ablation depth and anterior segment dimensions. Conclusion. Measurements with Sirius showed that ACA and ACV did not change; however, central ACD significantly decreased after myopic LASIK in young patients, indicating that the preoperative central ACD value should not be used interchangeably with the postoperative central ACD value.